Association between paraoxonase gene and stroke in the Han Chinese population - Zhang Guojun; Li Wenjin; Li Zhiqiang; Lv Hong; Ren Yonghong; Ma Ruimin; Li Xiaohong; Kang Xixiong; Shi Yongyong; Sun Yimin (BMC, 2013)
Abstract Background The human paraoxonase (PON) gene family has three isoforms: PON1, PON2 and PON3. These genes are implicated as potential risk factors of cerebrovascular disease and can prevent oxidative modification of low-density lipoproteins and atherosclerosis. This study evaluated the association between the genetic variants of all three PON genes and the risks of total stroke, ischemic stroke and hemorrhagic stroke in the Han Chinese population. Methods A total of 1016 subjects were recruited, including 508 healthy controls and 498 patients (328 with ischemic stroke and 170 with hemorrhagic stroke). A total of 11 single nucleotide polymorphisms (SNPs) covering the PON genes were genotyped for statistical analysis. Two of the 11 SNPs (rs662 and rs854560) were contextualized in a meta-analysis of ischemic stroke. Results The presence of rs705381 (−162) in the promoter region of PON1 was significantly associated with total stroke (Padjusted = 0.0007, OR = 0.57 [95% CI = 0.41-0.79]) and ischemic stroke (Padjusted = 0.0017, OR = 0.54 [95% CI = 0.37-0.79]) when analyzed using a dominant model, but was not associated with hemorrhagic stroke. There was also a nominal association between rs854571 (−824) and total stroke. Meta-analysis demonstrated a significant nominal association between rs662 and ischemic stroke, but there was no evidence of an association between rs662 and ischemic stroke risk in a single site association study. Conclusions These findings indicate that polymorphisms of PON1 gene may be a risk factor of stroke.